A rare presentation of a common disorder: severe hyponatremia presenting as reversible unstable bradyarrythmias - Md Pauzi, Ahmad Luqman; Mohamad Amin, Norhayati; Sazali, Adi Putera; Hashim, Juliana; Abdullah, Muhammad Afif; Ismail, Iskasymar; Wan Zukiman, Wan Zulhaikal (Universiti Putra Malaysia Press, 2024)
Severe hyponatraemia is defined as a sodium level of less than 120 mEq/L, and it is frequently accompanied by neurological symptoms like coma, convulsions, respiratory arrest, and death. Clinical cardiac toxicity from hyponatremia, such as bradyarrhythmia, is extremely rare. In this article, we present a case of acute severe hyponatraemia that induced unstable bradyarrhythmia and led to refractory bradycardia, which did not improve despite receiving treatment in accordance with the standard Advanced Cardiovascular Life Support protocol. The patient’s bradyarrhythmia has completely resolved with the administration of 3 hypertonic saline, which restored her sodium levels. Due to the possibility that severe hyponatremia may contribute to the aetiology of cardiac malfunction, this case raises awareness about the significance of closely monitoring electrocardiograms and telemetry in patients with severe hyponatremia.